SELF CONDEMNATION, INDEBTEDNESS AND FINANCIAL STRESS: FINDINGS OF A CROSSSECTIONAL STUDY IN PAKISTAN - Akhter, Syed Toqueer; Zaman, Huda Nadeem (European Scientific Journal, ESJ, 2015)
To determine various aspects of the Micro Economy that entails the foundation of Financial Stress arising for an individual in Pakistan. The essential focus of this study is firstly, on how behavioral factors or Personality Traits affect the degree of Financial Stress that an individual undergoes; and secondly, how conditions of Indebtedness of a person accentuate the conditions of distress. Assortments of constraints arising from Dependency burdens and Household Saving patterns that go hand-in-hand with the Economic Positionality are also brought into consideration with the help of this paper, focusing solely on results obtained for developing nations, such as Pakistan itself. Financial Stress was measured on a ten-item ordinal scale, consisting of a set of questions included in the survey questionnaire, while the preferred models used in this paper consisted of Ordered Probit and Tobit Models which estimated this cross-sectional study and the relationships of the two core variables; Self Condemnation, as well as Indebtedness with individuals’ financial stress. This study therefore, was able to depict that increased levels of Self Condemnation among individuals, due to a lack of resources or income, as well as high rates of Personal Debt in proportion to Individual Incomes; both have a positive significant relationship with the level of Financial Stress that these persons undergo. Government Policies and regulations of institutions can however, have an auspicious impact on the micro level as exploitation of the underprivileged can be controlled, and benefits be provided, leading to the uplifting of distress among the population.